PENDIDIKAN BAHASA INGGRIS UNTUK ANAK USIA DINI - Andi Asdar; Mujahidah (Jurnal Bastra (Bahasa dan Sastra), 2024)
This paper discusses English education for young learners (English for Young Learners – EYL). A person's ability to use English is highly essential in line with a nation's progress. Therefore, English education as an international language is now being introduced as early as possible to students in Indonesia. English education is ideally started from an early age, especially before they reach the age of 12. Early childhood refers to children aged 2–7 years. This age range is considered the golden period for language development. At this stage, children can learn any language like native speakers, making it crucial to maximize this period effectively. However, young children are still in the preoperational cognitive development stage, characterized by high egocentrism, an inability to understand abstract concepts, reliance on symbols, and pre-logical thinking. Therefore, EYL requires appropriate and effective teaching methods and processes. Several methods and techniques are suitable for teaching English to young learners, particularly in communicative contexts, including social and cultural situations, games, songs and music, storytelling, artistic experiences, crafts, and activities that emphasize physical movement. Among these methods and techniques, the approach using songs, singing, and movement has proven to be highly suitable and effective in English education for young learners